Fixed point theorems for nonself G-almost contractive mappings in banach spaces endowed with graphs - Jukrapong Tiammee (2018)
© 2016, North University of Baia Mare. All rights reserved. In this paper, we prove some fixed point theorems for non-self G-almost contractive mappings in Banach spaces with a directed graph and give some examples to illustrate our main results. The main results in this paper extend and generalize many known results in the literature therein.